2008
DOI: 10.1097/gme.0b013e318148b83e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogen therapy for 1 year on thyroid volume and thyroid nodules in postmenopausal women

Abstract: Estrogen administration for 1 year did not affect thyroid volume or the number and volume of thyroid nodules in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…The effect of estradiol and progesterone on thyroid morphology and function has been previously established (Kuhl et al 1985, Dalla Valle et al 1998, Krejza et al 2004, Sosić‐Jurjević et al 2005, Sekulić et al 2007). Estrogens have been shown to conflictingly exert stimulatory (Kuhl et al 1985, Furlanetto et al 1999), inhibitory (Sosić‐Jurjević et al 2005, Sekulić et al 2007), or no effects (Ceresini et al 2008) on thyroid activity, while progesterone was found to be not in synchronization with any oscillations of human thyroid flow velocity (Krejza et al 2004), although a vasoconstrictor effect on the blood vessels was suggested (Miyamoto et al 2005). The levels of estrogens and progesterone fluctuate markedly on a day‐to‐day basis during estrus in dolphins (Sawyer‐Steffan et al 1983, Robeck et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of estradiol and progesterone on thyroid morphology and function has been previously established (Kuhl et al 1985, Dalla Valle et al 1998, Krejza et al 2004, Sosić‐Jurjević et al 2005, Sekulić et al 2007). Estrogens have been shown to conflictingly exert stimulatory (Kuhl et al 1985, Furlanetto et al 1999), inhibitory (Sosić‐Jurjević et al 2005, Sekulić et al 2007), or no effects (Ceresini et al 2008) on thyroid activity, while progesterone was found to be not in synchronization with any oscillations of human thyroid flow velocity (Krejza et al 2004), although a vasoconstrictor effect on the blood vessels was suggested (Miyamoto et al 2005). The levels of estrogens and progesterone fluctuate markedly on a day‐to‐day basis during estrus in dolphins (Sawyer‐Steffan et al 1983, Robeck et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…(10,15) In contrast, others have detected a comparable ER-a expression in normal and tumor thyroid tissue. (18,19,28) It is worth mentioning that all these reports rely on IHC to determine the presence or absence of ER-a expression, and it is therefore interesting to note such a difference in the ER-a expression from different laboratories. One possibility is that such a technique is inadequate to obtain a definitive result when it comes to measure the presence of ER-a in thyroid lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The adequacy of iodine intake in this area was previously evaluated by measuring urinary iodine excretion in a sample of the population. Based on these results, a mild‐to‐moderate iodine deficiency was defined …”
Section: Methodsmentioning
confidence: 99%
“…Based on these results, a mild-tomoderate iodine deficiency was defined. 16 Cases were retrospectively identified from the Province Tumor Registry, which has been active since 1978 with an estimated 100% population coverage. Only patients identified by code C73.9 (indicating malignancy) of the International Classification of Diseases for Oncology, third edition, were included.…”
Section: Ate Ri Als An D Me Tho Dsmentioning
confidence: 99%